Pakistan : At the Crosscurrent of History - Ziring, Lawrence (Oxford, England Oneworld, 2003)
"Born from a vision of political idealism, caught up in turmoil from its first day of independence, this is the tale of one nation's journey from the margins of history to the center of the world stage. Forced into the spotlight by the international fight against terror, Pakistan has become a global player and an acknowledged nuclear power; today, struggling to balance Western influences with internal demands, it stands poised at the very crosscurrent of history." "Lawrence Ziring, political scientist and long-time observer of the Pakistan scene, combines all the salient facts with astute analysis to track Pakistan's history from the pre-Partition era, through Independence in 1947, to its changing role in the post-9/11 world. Guiding us through three wars, and numerous periods of political instability and martial law, he offers a penetrating analysis of the conflicts between tradition and modernity, religion and secularity, which continue both to burden this Muslim country and to shape its destiny."--
Include Maps and Index
Keywords: Politics and government -- Diplomatic relations